Impersonations : troubling the person in law and culture - Hamilton, Sheryl N., 1965- (University of Toronto Press, 2010)
Sheryl N. Hamilton uses five different kinds of persons - corporations, women, clones, computers, and celebrities - to discuss the instability of the concept of personhood and to examine some of the ways in which broader social anxieties are expressed in these case studies.